2020 International Conference on Electrical Machines (ICEM) 2020
DOI: 10.1109/icem49940.2020.9270829
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Airgap Length on Electromagnetic Performance of Surface Mounted Permanent Magnet Vemier Machine

Abstract: This paper investigates the effect of airgap length on the electromagnetic performance of 3kW surface mounted permanent magnet Vernier (SPM-V) machine. The performance is compared with a conventional surface mounted permanent magnet (SPM) machine with same airgap length using 2D Finite Element Analysis (2D FEA). For each airgap length, the slot/pole number combination for the SPM-V machine is investigated to achieve the optimal performance compared to the conventional SPM machine. The results show that the SPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…3kW, 3MW and 10MW, which has not been reported in the literature. This paper is an extension of the original work presented in [18]. An outer rotor topology, for example, the schematic shown in Fig.…”
Section: Windingmentioning
confidence: 98%
“…3kW, 3MW and 10MW, which has not been reported in the literature. This paper is an extension of the original work presented in [18]. An outer rotor topology, for example, the schematic shown in Fig.…”
Section: Windingmentioning
confidence: 98%
“…The literature review revealed that a vast majority of research works about PM-V machines have been focused on small power ratings in the range of a few kWs. Recently, a few research works investigating the feasibility of PM-V machines for multi-MW direct-drive wind power applications have been published [19]- [24]. This section is dedicated to summarizing the challenges and benefits unfolded in these papers while scaling the PM-V machines from few kWs up to multi-MW power levels.…”
Section: Challenges and Benefits Of Pm-v Machines For Direct-drive Of...mentioning
confidence: 99%
“…The assessment of the torque ripple is very critical for lowspeed high torque direct-drive applications. Similar to low power ratings, the torque ripple of the SPM-V machines was found to be inherently lower than the conventional SPM machines even at multi-MW power levels [20], [24]. The comparison was made without incorporating any torque ripple reduction techniques like PM shaping, skewing, etc.…”
Section: A Torque and Torque Ripplementioning
confidence: 99%
See 2 more Smart Citations